Hemorrhoids - Norman E Marcon (Canadian Journal of Gastroenterology)
Hemorrhoids are vascular spaces forming cushions above the anal canal which allow the passage of gas without stool, and cause clinical problems only when they become engorged and prolapse with resulting pain, bleeding, itching or discharge. Hemorrhoids require treatment only if they cause symptoms, and should be treated only as long as symptoms persist. Techniques of treatment including injection therapy, rubber band ligation, infrared coagulation, bipolar probe, heater probe, ultroid and YAG laser are described. At present, rubber banding is the most cost effective therapy. Diet education is essential to prevent recurrence.